改性秸秆灰负载Pt催化甘油氧化性能研究Glycerol oxidation catalyzed by modified straw ash supported Pt - 王聪莹1， 于静2， 崔佳欣1 WANG Congying1，YU Jing2，CUI Jiaxin1 (Zhongguo youzhi)
为实现生物质高值利用，采用碱改性、酸改性、酸碱联合改性和引入CeO2的方法对秸秆灰进行前处理，制备Pt基催化剂（分别命名为Pt/ash-b、Pt/ash-a、Pt/ash-ba和Pt/ash-CeO2），通过X射线荧光光谱（XRF）、X射线衍射（XRD）、电感耦合等离子原子发射光谱（ICP-OES）、透射电子显微镜（TEM）、CO2程序升温脱附（CO2-TPD）和NH3程序升温脱附（NH3-TPD）、氢气程序升温还原（H2-TPR）测定催化剂的组成、结构、Pt负载量、Pt颗粒粒径、表面酸碱性、Pt还原活性，并考察催化剂催化甘油氧化的性能。结果表明：与未改性催化剂（Pt/ash）相比，酸、碱改性分别提高了Pt/ash-a中SiO2的含量和Pt/ash-b中Na2O的含量至73.61%和12.51%，Pt/ash-CeO2中的Na2O 含量（18.92%）高于CeO2的引入量（2.96%）；各催化剂中Pt的实际负载量（约0.05%）和颗粒平均粒径（1.5~2.3 nm）较为接近；CO2-TPD和NH3-TPD结果证明碱处理和引入CeO2得到的Pt/ash-b和Pt/ash-CeO2表面碱性位点数量明显增加；H2-TPR结果表明Pt/ash-CeO2中CeO2的负载增强了Pt物种的还原能力；Pt/ash-b和Pt/ash-CeO2在碱性条件下甘油转化率（30.8%和29.7%）较高，证明碱性位点数量的增加有利于提高催化剂对甘油的转化率；在非碱性条件下，Pt/ash-CeO2表现出最高的甘油转化率（25.2%），甘油酸选择性为32.4%，甘油醛选择性为27.5%，表明Pt/ash-CeO2中Pt还原能力的提高有利于甘油伯羟基氧化生成甘油醛，进一步氧化生成甘油酸；Pt/ash-CeO2在非碱性条件下循环使用5次后稳定性良好。综上，CeO2的引入有效调节了秸秆灰负载Pt催化剂的酸/碱性位点，提高了Pt的活性与对甘油醛和甘油酸的选择性。 In order to achieve high value utilization of biomass, Pt-based catalysts of Pt/ash-b, Pt/ash-a, Pt/ash-ba and Pt/ash-CeO2 were prepared by pre-treating straw ash using alkali modification, acid modification, combined acid and alkali modification, and introduction of CeO2, respectively. The composition, structure, loading amount of Pt, size of Pt particle, surface acidity and alkalinity, and Pt reduction activity of the catalysts were determined by X-ray fluorescence spectroscopy (XRF), X-ray diffraction (XRD), inductively coupled plasma-atomic emission spectroscopy (ICP-OES), transmission electron microscopy (TEM), CO2 programmed temperature-raising desorption (CO2-TPD) and NH3 programmed temperature-raising desorption (NH3-TPD), and hydrogen-programmed temperature-raising reduction (H2-TPR), respectively. In addition, the catalytic performance of the catalysts for the oxidation of glycerol was investigated. The results showed that acid and alkali modification increased the content of SiO2 in Pt/ash-a and Na2O in Pt/ash-b to 73.61% and 12.51%, respectively, compared with the unmodified catalyst (Pt/ash). The content of Na2O in Pt/ash-CeO2 (18.92%) was higher than the introduction of CeO2 (2.96%). The actual loading amount of Pt (about 0.05%) and the average diameter of Pt particle size (1.5-2.3 nm) were closer in each catalyst. CO2-TPD and NH3-TPD results demonstrated that the number of base sites on the surface of the Pt/ash-b and Pt/ash-CeO2 catalysts obtained by alkali treatment and introduction of CeO2 significantly increased. H2-TPR results showed that the loading of CeO2 in the Pt/ash-CeO2 catalysts enhanced the reduction capacity of the Pt species. The Pt/ash-b and Pt/ash-CeO2 in the glycerol conversion (30.8% and 29.7%) were higher under alkaline conditions, which proved that the increase in the number of base sites was beneficial to improve the conversion of glycerol by the catalysts. Under non-alkaline conditions, the Pt/ash-CeO2 catalyst exhibited the highest glycerol conversion (252%), with a glyceric acid selectivity of 32.4% and a glycerol aldehyde selectivity of 27.5%, suggesting that the increase in the Pt reduction capacity in Pt/ash-CeO2 facilitated the oxidation of the primary hydroxyl group of glycerol to produce glycerol aldehyde, which was further oxidized to produce glycerol acid. Pt/ash-CeO2 had good stability after 5 cycles under non-alkaline conditions. In summary, the introduction of CeO2 effectively regulates the acid/base sites of the straw ash supported Pt catalysts and improved the activity of Pt and selectivity for glycerol aldehyde and glyceric acid.